Innate Immune Regulation by Toll-Like Receptors in the Brain. (14th October 2012) - Mallard, Carina
Abstract : The innate immune system plays an important role in cerebral health and disease. In recent years the role of innate immune regulation by toll-like receptors in the brain has been highlighted. In this paper the expression of toll-like receptors and endogenous toll-like receptor ligands in the brain and their role in cerebral ischemia will be discussed. Further, the ability of systemic toll-like receptor ligands to induce cerebral inflammation will be reviewed. Finally, the capacity of toll-like receptors to both increase (sensitization) and decrease (preconditioning/tolerance) the vulnerability of the brain to damage will be disclosed. Studies investigating the role of toll-like receptors in the developing brain will be emphasized.